2017
DOI: 10.1186/s12888-017-1525-6
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the systematic medical appraisal, referral and treatment (SMART) mental health project in rural India

Abstract: BackgroundAvailability of basic mental health services is limited in rural areas of India. Health system and individual level factors such as lack of mental health professionals and infrastructure, poor awareness about mental health, stigma related to help seeking, are responsible for poor awareness and use of mental health services. We implemented a mental health services delivery model that leveraged technology and task sharing to facilitate identification and treatment of common mental disorders (CMDs) such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 11 publications
3
63
2
1
Order By: Relevance
“…Firstly, we found no evidence that those with lower levels of self-stigma, exposure to mental health communications, or indicators of higher mental health literacy were more likely to seek treatment for depression. This contrasts with the conclusions of previous Indian studies, which have implicated these factors as barriers to treatment-seeking (13,61). This may be because in the current study research workers referred to specific symptoms of depression, rather than to mental illness or psychiatric treatment, and some evidence suggests that symptoms of common mental disorders are not associated with mental illness in India (41).…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 99%
See 1 more Smart Citation
“…Firstly, we found no evidence that those with lower levels of self-stigma, exposure to mental health communications, or indicators of higher mental health literacy were more likely to seek treatment for depression. This contrasts with the conclusions of previous Indian studies, which have implicated these factors as barriers to treatment-seeking (13,61). This may be because in the current study research workers referred to specific symptoms of depression, rather than to mental illness or psychiatric treatment, and some evidence suggests that symptoms of common mental disorders are not associated with mental illness in India (41).…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 99%
“…Secondly, while a majority of participants felt that cost and distance barriers are important, in line with previous research (13,61,63), those who reported these barriers were no less likely to seek treatment for depression. We also found little evidence to support differences in treatment-seeking by socio-economic status.…”
Section: Who Seeks Health Care For Depression Symptoms?supporting
confidence: 72%
“…Other implementation strategies commonly tested included facilitating the relay of clinical data to providers (n = 3; 14.3%) and conducting ongoing training (n = 3; 14.3%). For example, Tewari et al (2017) reported the acceptability, feasibility, and fidelity of a community-based electronic decision-support implementation strategy to facilitate the relay of clinical depression data from the community to primary care providers in India. Gureje et al (2015) reported fidelity associated with the conducting ongoing training of primary healthcare workers in the WHO Mental Health Gap Action Programme Intervention Guide to integrate depression treatment with primary care in Nigeria.…”
Section: Implementation Strategy Characteristicsmentioning
confidence: 99%
“…Yet, even with this widespread recognition of MNS disordersand depression in particularas key drivers of global disability, the gap between knowledge of evidence-based prevention and treatment approaches in the literature and its application in community settings is large. In high-income settings, only one in five patients with depression receive minimally-adequate treatment, with gaps increasing to one in nine in upper-middle-income countries and 1 in 27 for lower-middle-income countries (Thornicroft et al, 2017). Others have written that a comprehensive 'mental health care gap' would likely be much larger, as it would include the biomedical treatment gap, combined with the psychosocial care gap as well as the physical health care gap (Pathare et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The process evaluation from the set of 30 villages indicates that the intervention is acceptable, feasible and can be scaled up. It has identified a set of barriers and facilitators which need to be addressed 22 . Future randomised controlled studies can address these issues, add to the evidence and provide data on cost effectiveness so that this methodology could then be applied across similar settings after suitable adaptations.…”
Section: Discussionmentioning
confidence: 99%